On the Nature of Gravity Currents - Tjipto Prastowo (Institut Teknologi Bandung, 2009)
A series of laboratory experiments are used to examine the nature of a gravity current propagating along the base of a horizontal channel. The shear instability formed at the interface between two counter-flowing layers generates turbulence and mixing, particularly above the head of the current. While the resulting mixing is in part examined through its effects on the flow dynamics, the characteristics of the gravity current is determined by measuring the depth and speed of the current. The results for both shallow and deep currents reveal that the current depth is found to be 0.36-0.47 H, where H is the full water depth. The non-dimensional current speed is measured to be 0.48Â±0.02, independent of flow processes and dynamic variables.